The roles of color and lighting in developing inclusive library learning environments for deaf users - Dewi, Riza Septriani; Faridah, Eulis Yulianti (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. This study examines how DeafSpace principles, including color and lighting, can create equal educational opportunities for deaf library users. By examining fourth-floor reading room of UIN Sunan Kalijaga Library, the research addresses a significant gap in inclusive design literature that has given insufficient attention to visual elements as communication tools. The findings offer crucial insights for advancing disability rights and establishing inclusive library design standards that cater to all users. Research Methods. A practice-based research method with a three hybrid design framework approach was used to identify color and light concepts that enhance the self-sufficiency of deaf library users. Data Analysis. Data was collected through interviews and questionnaires using a Likert scale, with the findings analyzed descriptively. Results. This study shows that cool colors, particularly green, and evenly distributed lighting significantly enhance the emotional experience of deaf library users navigating these spaces independently. The implications for inclusive design are meaningful: libraries that thoughtfully apply appropriate color palettes and optimize lighting conditions create environments where deaf users can comfortably achieve their full academic potential and productivity. Conclusion. This research developed a conceptual design model for library reading spaces, optimizing color and lighting to enhance independence, accessibility, and support for deaf users in higher education.